2015
DOI: 10.1186/s13287-015-0196-9
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Bmi1 + cells contribute to myocardial renewal in the murine adult heart

Abstract: IntroductionThe mammalian adult heart maintains a continuous, low cardiomyocyte turnover rate throughout life. Although many cardiac stem cell populations have been studied, the natural source for homeostatic repair has not yet been defined. The Polycomb protein BMI1 is the most representative marker of mouse adult stem cell systems. We have evaluated the relevance and role of cardiac Bmi1+ cells in cardiac physiological homeostasis.MethodsBmi1CreER/+;Rosa26YFP/+ (Bmi1-YFP) mice were used for lineage tracing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 53 publications
2
53
0
Order By: Relevance
“…Agreed with our findings, Valiente‐Alandi I et al has crossed the Bmi‐1 CreER/+ strain with Rosa26 YFP/+ reporter mice to generate Bmi‐1 CreER/+ ;Rosa26 YFP/+ (Bmi‐1‐YFP) mice for cardiac lineage tracing, and demonstrated that Bmi‐1 + cells contribute to myocardial renewal and myocardial repair following acute injury . Furthermore, Bmi‐1 expression is associated with reactive oxygen species levels .…”
Section: Discussionsupporting
confidence: 82%
“…Agreed with our findings, Valiente‐Alandi I et al has crossed the Bmi‐1 CreER/+ strain with Rosa26 YFP/+ reporter mice to generate Bmi‐1 CreER/+ ;Rosa26 YFP/+ (Bmi‐1‐YFP) mice for cardiac lineage tracing, and demonstrated that Bmi‐1 + cells contribute to myocardial renewal and myocardial repair following acute injury . Furthermore, Bmi‐1 expression is associated with reactive oxygen species levels .…”
Section: Discussionsupporting
confidence: 82%
“…including those in the heart. [19] BMI1 acts as an epigenetic repressor, remodeling chromatin through histone monoubiquitination [20] Among its main targets, PCR1 represses Hox, p16 INK4a and master differentiation genes [21,22]. Additional PCR1 functions are described in mammalian somatic cells; BMI1 is needed for constitutive heterochromatin formation [23] and is recruited to DNA breaks after DNA damage [24].…”
Section: Introductionmentioning
confidence: 99%
“…1H, histogram), when the mature endothelial and SMC differentiation occurs. Expression of bmi1, a member of the Polycomb repressive complex 1 and a known stem cell self-renewal marker [28,29], was increased by PK2 treatment of hEPDCs ( Fig. 1I).…”
Section: Role Of Pk2 In Hepdcs Stemnessmentioning
confidence: 97%